Hubungan Etika Kerja Islam Dan Kemampuan Kerja Karyawan Dengan Produktivitas Kerja Karyawan Pada Bank Syariah Bukopin Surabaya Cabang Darmo - Rahman , Fathor; Cahyono, Hendry (Jurnal Ekonomika dan Bisnis Islam, 2019)
Employees are the most important factor to maximize quality and productivity. One instrument to increase productivity by means of work ethics and work ability. This research is a quantitative research that correlates usability to know whether there is or is not a relationship with ethics and the ability to work with productivity. The data used in this study are primary data obtained from questionnaires issued for Bank Syariah Bukopin Surabaya employees and interviews. From the results of the research conducted, it shows that, there was a strong and significant relationship islamic work ethics with employee work productivity, there was a strong and significant relationship work ability with employee work productivity and there was a very strong and significant relationship between islamic work ethics and work ability with employee work productivity.